Walter Benjamin and Sigfried Giedion Constructive Unconscious - Déotte, Jean-Louis (Revista de Humanidades de Valparaíso, 2013)
Walter Benjamin proposed as aesthetic and political objective to determine the axis of the common sensibility of the nineteenth century, based on the work of Sigfried Giedion: Bauen in Frankreich (1928). Giedion’s works have since formed generations of architects, as a result of its international at the head of the International Congresses of Modern Architecture position.